Do Epigenetic Changes Drive Corticosterone Responses to Alarm Cues in Larvae of an Invasive Amphibian?. (16th June 2020) - Sarma, Roshmi R; Edwards, Richard J; Crino, Ondi L; Eyck, Harrison J F; Waters, Paul D; Crossland, Michael R; Shine, Richard; Rollins, Lee A
Synopsis: The developmental environment can exert powerful effects on animal phenotype. Recently, epigenetic modifications have emerged as one mechanism that can modulate developmentally plastic responses to environmental variability. For example, the DNA methylation profile at promoters of hormone receptor genes can affect their expression and patterns of hormone release. Across taxonomic groups, epigenetic alterations have been linked to changes in glucocorticoid (GC) physiology. GCs are metabolic hormones that influence growth, development, transitions between life-history stages, and thus fitness. To date, relatively few studies have examined epigenetic effects on phenotypic traits in wild animals, especially in amphibians. Here, we examined the effects of exposure to predation threat (alarm cues) and experimentally manipulated DNA methylation on corticosterone (CORT) levels in tadpoles and metamorphs of the invasive cane toad ( Rhinella marina ). We included offspring of toads sampled from populations across the species' Australian range. In these animals, exposure to chemical cues from injured conspecifics induces shifts in developmental trajectories, putatively as an adaptive response that lessens vulnerability to predation. We exposed tadpoles to these alarm cues, and measured changes in DNA methylation and CORT levels, both of which are mechanisms that have been implicated in the control of phenotypically plastic responses in tadpoles. To test the idea that DNA methylation drives shifts in GC physiology, we also experimentally manipulated methylation levels with the drug zebularine. We found differentially methylated regions (DMRs) between control tadpoles and their full-siblings exposed to alarm cues, zebularine, or both treatments. However, the effects of these manipulations on methylation patterns were weaker than clutch (e.g., genetic, maternal, etc.) effects. CORT levels were higher in larval cane toads exposed to alarm cues and zebularine. We found little evidence of changes in DNA methylation across the GC receptor gene ( NR3C1 ) promoter region in response to alarm cue or zebularine exposure. In both alarm cue and zebularine-exposed individuals, we found differentially methylated DNA in the suppressor of cytokine signaling 3 gene ( SOCS3 ), which may be involved in predator avoidance behavior. In total, our data reveal that alarm cues have significant impacts on tadpole physiology, but show only weak links between DNA methylation and CORT levels. We also identify genes containing DMRs in tadpoles exposed to alarm cues and zebularine, particularly in range-edge populations, that warrant further investigation.